Fasting and postprandial gastrointestinal motility in ulcer and non-ulcer dyspepsia. Issue 2 (February 1992) - Stanghellini, V; Ghidini, C; Maccarini, M R; Paparo, G F; Corinaldesi, R; Barbara, L
Abstract : This study aimed to compare fasting and postprandial gastrointestinal motor patterns in patients with ulcer and non-ulcer dyspepsia. Forty five subjects were studied: 10 with uncomplicated gastric ulcer, eight with uncomplicated duodenal ulcer, 18 with chronic idiopathic dyspepsia, and nine healthy asymptomatic controls. Gastrointestinal fasting and postprandial motor patterns were recorded using a low compliance perfusion technique. The interdigestive antral cumulative motility index, computed for 30 minutes before the appearance of duodenal activity fronts, and the number of activity fronts with an antral component were significantly less in patients with ulcers and those with non-ulcer dyspepsia compared with asymptomatic controls. The patient groups also had a reduced antral motor response to a solid-liquid test meal compared with healthy controls. Intestinal motor abnormalities (bursts of non-propagated phasic pressure activity and discrete clustered contractions) were recorded in a minority of patients, all with associated irritable bowel symptoms. In conclusion, antral hypomotility is a frequent but nonspecific motor abnormality in dyspepsia; abnormal motor patterns of the small bowel are less frequent and seem to be confined to patients with concomitant irritable bowel syndrome.